15-Deoxi-∆12,14-prostaglandina J2 (15d-PGJ2) reduz a produção de IL-8 induzida por alérgenos do ácaro Dermatophagoides pteronyssinus em linhagem de queratinócitos humanos - Borges, Hellen Dayane Silva (2017)
Atopic dermatitis (AD) is a chronic inflammatory skin disease with a high incidence worldwide. The pathogenesis of AD is complex, involving interactions between genetic susceptibility, changes in the skin barrier, immunological and environmental factors, especially exposure to the domestic dust mite such as Dermatophagoides pteronyssinus (Dpt). Keratinocytes participate in the immunoregulation of AD, through secretion of cytokines, chemokines and expression of receptors involved in inflammatory reactions. The human skin expresses the three types of PPAR receptors (PPARa, PPARP and PPARy).) PPAR agonists have anti-inflammatory properties because they reduce the expression of various proinflammatory cytokines, chemokines and cell adhesion molecules. Cyclopentenone 15-deoxy D 12, 14-PGJ 2 (15d-PGJ 2), an endogenous proliferator-activated peroxisome receptor (PPARy) intranuclear receptor ligand has already shown anti-inflammatory effects in different cell lines. The objective of this study was to evaluate the immunomodulatory capacity of 15d-PGJ2 in the production of inflammatory cytokines mediated by the Dpt extract in human keratinocyte line (HaCat cells). Dithiotreitol-DTT (aDpt) activated Dpt or Dpt treatment induced the production of IL-8 in a dose-dependent manner, being aDpt the most potent inducer IL-8. Pretreatment with 15d-PGJ2 showed a significant reduction of IL-8 and IL-6 levels induced by aDpt. We conclude that pre-treatment with 15d-PGJ2 promotes the down- regulation of aDpt-induced IL-8 and IL-6 production in HaCat cells, allowing further use in the development of novel therapies for the disease.